Hubungan Kerapatan Lamun dengan Kepadatan Gastropoda Pada Habitat Lamun Di Perairan Desa Tayando Yamtel Kecamatan Tayando Yamtel Kota Tual - Liyatin Gea; Muhamad Hariono (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2022)
The gastropod community is an important component in the food chain in seagrass beds, where gastropods are basic detritus feeders. The presence of gastropods is largely determined by the presence of seagrass vegetation in coastal areas. Research on the relationship between seagrass density and gasrtopod density in the waters of Tayando Yamtel Village, Tam District, Tual City, was conducted in March-May 2018, using the quadrant linear transect method. The results of the research on the relationship between seagrass density and gasrtopod density obtained a correlation value at station I, obtained a 2-tailed significance value > 0.05 indicating a sufficient/moderate degree of relationship (r = 0.441) and the direction of the relationship was positive. While at stations II (r = -0.778) and III (r = -0,308) showed a 2-tailed significance value <0.05 with a very weak degree of relationship and a negative direction of relationship.